Witnessing the Great War in Britain: Centenaries and the Making of Modern Identities - Ross J. Wilson (Anglica. An International Journal of English Studies)
As the centenaries of the events of the Great War are commemorated in Britain, a wave of new memorials and commemorative practices have been developed. These are additions to an already well-established ‘landscape of memory,’ with memorials built in the war’s immediate aftermath across villages, towns and cities in Britain. This article examines these new sites of memory and mourning to reveal how social, moral and political identities within contemporary Britain are constructed through places that enable individuals and communities to ‘bear witness’ to the conflict.